Perbaikan Proses Bisnis Dengan Menggunakan Metode Business Process Improvement Pada Konveksi Pager Kaos - Hidayat, Fajar Sidiq; Chumaidiyah, Endang; Sulistyo, Budi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Pager Kaos is a conventional enterprise that provides services in the manufacture of clothes and templates. The business process in the business at Pager Kaos is still not optimal, mainly the activity carried out on the ordering process, which still takes quite a long Time and results in repeated activity. Problems arise because my resources of people, facilities, and technology that have not been optimally utilized. So there's a need for improvement, which is to make improvements to the business process. Improvement of business processes on the Chaos Pager Convention is done using Business Process Improvements (BPI). Focus methods to help companies improve business processes to be more effective and efficient. The main business processes observed are the ordering process, production process, packaging and delivery process, and financial recording. From these processes, each activity is analyzed so that it can be grouped according to RVA, BVA, and NVA, and cycle Time efficiency calculations and streamlining are performed to obtain business process improvements. To support the improvement of business processes, a Google form and spreadsheet-based application were designed to help in the process of recording incoming orders and recording order data, as well as in storing photos and videos of customer order documentation to be more organized. The result of the improvement affects the number of previous activities, which were reduced to 30. The cycle Time has been reduced from the previous 178,66 minutes to 149,49 minutes. The previous business process efficiency of 72,61% increased to 80,47%.